Contribuições do PIBID Biologia da Universidade Federal de Uberlândia para a formação política do professor de Ciências e Biologia - Ferrari, Pedro Henrique Parada (2015)
This work, was carried out in the Graduation in Education Program of the Uberlândia Federal University. It aims to investigate the contributions of the Introduction to Biology Teaching - Scholarship Institutional Program for the political formation of Biology teacher. The research is committed to the Materialistic-historic-dialectic perspective which guides epistemologically this study and makes use of technical procedures for the collection of data: Documental analysis, state of art about PIBID s articles and interviews with. Contradictions were aised in the textual mapping and grouped in categories for the preparation of the synthesis of ideas, contextualizing them to the theory. The analysis involved three steps after the collection of interviews data: pre-analysis, exploration of material and interpretation. The PIBID program has a potential to catalyze group debates about the teaching profession, but shows weakness on the sociopolitical fellows formation of the pibidianos. Much of the program of discussion and debate continues playing without addressing the productive system, towards a formation based on the instrumentalization of the teaching practice that aims to improve the teaching-learning process disconnected from the history of the reality. It is possible to notice that the fellows are formed to accept the working conditions of the teaching profession, an exercise in a constant precarization process. Nevertheless, the fellows received instructions to have the function of play contents to the formation of students. The absence of studies in the several areas of the teacher development makes it impossible to understand the morphology of the work and ends up forming disabled and unilateral professionals, which transforms the job of a professor as a mere classroom acting. The formation of a teacher is mainly understood as the accumulation of teaching techniques, proposal of innovative lessons, and constant updating with new technologies, causing a false sensation that education is being put in a transforming perspective. The fellows do not adhere to a philosophical framework, keeping their practices anchored to an epistemic eclecticism, what keeps them away from a political understanding of own formation. The inclusion of the fellows in the school environment empowers the glimpse of the contradictions in the world of work. However, the school experiences do not guarantee an education that articulates the whole and the parts, and the parts of the whole in the teacher development. The PIBID is a project with potential for reflexive maturation concerning the teacher s work because it penetrates the school environment and inserts the fellows there, even partly, into the world work.